CREATING ALGORITHM FOR SIMULATION OF FORMING FLAT WORKPIECES - Solomonov, Konstantin; Lezhnev, Sergey (Informatyka, automatyka, pomiary w gospodarce i ochronie środowiska, 2015)
Problems of creating of the algorithm and software for the simulation of some metal forming processes are considered. The results obtained in the simulation of the flow pattern of metal for processes of forging and stamping flat workpieces are represented.